PENGEMBANGAN KAWASAN WISATA PANTAI BARON KABUPATEN GUNUNGKIDUL - , FANDA MAXIMILIANS SOMPIE ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to identify periodicity / phase of development and all efforts done by various parties in the development of Area Tourism Baron beach, and to identify factors affecting these developments. This is case study was success. The unit of information as a key figure is the Local Government Gunungkidul, Kemadang Village Government, Craftsmen Shells, Fishermen's Society Group (POKDARWIS) who play a role in the coastal resorts Baron. Baron beach resort area development can be seen from the 3 (three) developmental stages, namely (1) Pre Reboization